Applying the island transport equivalent to the Greek islands - Lekakou Maria; Remoundos George; Stefanidaki Evangelia (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2021)
This report looks at the need for Greece to redesign its inter-island transport system to make it more operational and sustainable. It takes into account the challenges of designing networks for island ecosystems and island clusters, which present even greater difficulties. Specifically, it examines applying the Island Transport Equivalent policy tool to increase island accessibility and growth potential.
Keywords: 330; Logistikdienstleister; Transportmanagement; Insel; Griechenland